Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12864-016-2666-6
|View full text |Cite
|
Sign up to set email alerts
|

Ostreococcus tauri is a new model green alga for studying iron metabolism in eukaryotic phytoplankton

Abstract: BackgroundLow iron bioavailability is a common feature of ocean surface water and therefore micro-algae developed original strategies to optimize iron uptake and metabolism. The marine picoeukaryotic green alga Ostreococcus tauri is a very good model for studying physiological and genetic aspects of the adaptation of the green algal lineage to the marine environment: it has a very compact genome, is easy to culture in laboratory conditions, and can be genetically manipulated by efficient homologous recombinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 76 publications
(114 reference statements)
4
27
0
Order By: Relevance
“…Three clades of Ostreococcus —A, C and D—are classified as high-light adapted, as defined through laboratory photophysiology assessments, and clade B is described as low-light adapted [40]. However, this low-light adapted clade has been reported in surface waters [8,43] and although different ecotypes do not commonly occur at the same geographical location, the drivers behind clade distribution may be more complex than determined by sea surface irradiance levels alone [43]. The putative low-light ecotype strain has increased photosensitivity and an adapted photoprotection mechanism.…”
Section: Prasinophyte Host Genomes and Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…Three clades of Ostreococcus —A, C and D—are classified as high-light adapted, as defined through laboratory photophysiology assessments, and clade B is described as low-light adapted [40]. However, this low-light adapted clade has been reported in surface waters [8,43] and although different ecotypes do not commonly occur at the same geographical location, the drivers behind clade distribution may be more complex than determined by sea surface irradiance levels alone [43]. The putative low-light ecotype strain has increased photosensitivity and an adapted photoprotection mechanism.…”
Section: Prasinophyte Host Genomes and Ecologymentioning
confidence: 99%
“…TEM analysis confirmed viruses are localised to a region of the cytoplasm and do not associate with the nucleus or other organelles [30]. Ostreococcus and their viruses are globally distributed in coastal and open-ocean euphotic environments [34,36,43]. Viruses that infect O. tauri have been reported to be prevalent in coastal sites [32,33,36], whilst OlVs have been detected in more widespread marine locations, including oligotrophic sites in the Atlantic and Pacific Oceans [34,36,71,72], although this geographical distribution is not related to genetic distance, based on analysis of the polB gene [36].…”
Section: Ostreococcus and Its Viruses As A Host–virus Modelmentioning
confidence: 99%
“…These transporters belong to a mix of protein families with origins in various lineages and unique phylogenetic occurrences (Figure 2). For instance, Fe uptake at the plasma membrane occurs by a reduction-oxidation-transport mechanism, involving FRE1 (Fe reductase), FOX1 (Fe oxidase) and FTR1 (permease) [1519], which is found in other algae, such as rhodophytes and diatoms [20], but absent from most land plants and prasinophytes [21,22] (Figure 2A). Additional components of high-affinity Fe uptake include the soluble secreted proteins FEA1 and FEA2, which are only found in the algal lineages [17,23,24].…”
Section: Border Controlmentioning
confidence: 99%
“…Instead of Fe-storage, these ferritins are proposed to mediate an Fe-sparing/recycling process involving degradation of the Fe-rich photosystem I (PSI) complex [37]. The Ostreococcus tauri ferritin appears to play a similar role in buffering Fe in the chloroplast (rather than storage) as a function of the day/night cycle [22,38]. Although ferritin is central to iron homeostasis in both green algae and diatoms [39], it is not found in all algal genomes (Figure 4B).…”
Section: Stockpiles and Quarantinesmentioning
confidence: 99%
“…We recently unveiled a central role for ferritin in the day-night regulation of iron homeostasis in the picoeukaryotic alga Ostreococcu s tauri and showed that the transcriptional response to iron limitation in this microorganism is tighly dependent on the diurnal cycle 17, 18 . Still, the adaptive responses of eukaryotic picophytoplankton to low iron conditions remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%